Decoding futsal offensive game moments: an in-depth qualitative study with expert coaches - Rodrigues, M.; Ramos, A.; Leite, N.; Ribeiro, J. N.; Araújo, D.; Travassos, B. (International Journal of Performance Analysis in Sport, 2025)
Purpose: In futsal, coaches must make decisions in unpredictable contexts by continuously selecting the most relevant information to understand the game dynamics. This study aims to characterise and interpret what elite futsal coaches perceive as critical information. Specifically, per each game moment, it was intended to explore the coaches` perceptions about what is the critical information presented. Methods: Ten expert futsal coaches (48.30 ± 5.85 years; experience 18.10 ± 4.12 years) that currently coach elite futsal teams were selected. A total of 37 video clips were selected and exhibited. Qualitative data was obtained through semi-structured interviews and analysed by content analysis. Results: The findings portrayed expert coaches identified and interpreted different informational constraints as critical according to the environment of play. In detail, to explain the attack, coaches perceived the information related with the defensive system. Also, most of the information highlighted was related with individual actions that sustains team`s behaviour in relation to the opponent. Conclusion: The informational constraints that support coaches` perception about each game moment were specific to each play circumstances. Thus, we emphasised the need for coach education courses to master the interplay between knowledge about and knowledge of the environment, in developing novice coaches.